Maritime strategic thinking : The GIUK example - Masala, Carlo (Metis Institute for Strategy and Foresight, Bundeswehr University Munich, 2020)
After years of neglect, the GIUK Gap is now once more receiving the attention it deserves from the security community. Although its significance with regard to the Arctic is likely to change in the future, this area in the North Atlantic remains a strategically important line of communication and transportation for the US and Europe. This study anticipates possible strategic courses of action for NATO.